1996
DOI: 10.1111/j.1468-0092.1996.tb00072.x
|View full text |Cite
|
Sign up to set email alerts
|

Problems of Phasing: A Reconsideration of the Black Patch Middle Bronze Age ‘Nucleated Village’

Abstract: The Middle Bronze Age settlement complex of Black Patch, East Sussex, originally considered to represent the remains of a single phase 'nucleated village', is here reconsidered as representing the remains. of two chronologically distinct settlement units. The dangers inherent in overlooking sequence and assuming contemporaneity for all archaeological features revealed within the course of a single excavation, are outlined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 4 publications
1
6
0
Order By: Relevance
“…At Itford Hill the settlement has been interpreted (Ellison 1978) as shifting five times but retaining roughly the same composition of houses and retaining a continued interest in place. A similar interpretation has been suggested for the site at Blackpatch (Russell 1996) where it has been argued the two principal houses were replaced by houses that were placed in between the original 105…”
Section: Niall Sharpiessupporting
confidence: 58%
“…At Itford Hill the settlement has been interpreted (Ellison 1978) as shifting five times but retaining roughly the same composition of houses and retaining a continued interest in place. A similar interpretation has been suggested for the site at Blackpatch (Russell 1996) where it has been argued the two principal houses were replaced by houses that were placed in between the original 105…”
Section: Niall Sharpiessupporting
confidence: 58%
“…In southern and south-eastern England Middle Bronze Age sites such as Itford Hill and Black Patch in Sussex, and Thorny Down, Wiltshire, were originally considered to be small villages, but later analysis suggested that the chronological depth of the sites had been missed, and that in each case only a handful of the buildings were occupied simultaneously (Burstow & Holleyman 1957; Drewett 1982; Ellison 1987, 391; Russell 1996, 35–7; Stone 1941, 117). Brück's in-depth analysis of Middle Bronze Age settlements in southern England concluded that: ‘most were occupied by a single household, perhaps comprising a nuclear or small extended family group’ (Brück 1999, 145–7).…”
Section: Bronze Age Villages: the Definite And The Dubiousmentioning
confidence: 99%
“…At many sites, there are clear indications of chronological depth. Over the years, buildings were constructed, refurbished and abandoned, fences erected and dismantled and ponds dug and infilled (Ellison 1978; Barre� et al 1991, section 5.3;Russell 1996). Such sequences of construction can most convincingly be explained through reference to changes in the demographic, social and economic circumstances of the household over the course of its developmental cycle (Brück 1999;cf.…”
Section: Se�lement Lifecyclesmentioning
confidence: 99%